What Predicts Software Developers' Productivity? - Murphy-Hill, Emerson; Jaspan, Ciera; Sadowski, Caitlin; Shepherd, David; Phillips, Michael; Winter, Collin; Knight, Andrea; Smith, Edward; Jorde, Matthew (IEEE transactions on software engineering, 2021)
Organizations have a variety of options to help their software developers become their most productive selves, from modifying office layouts, to investing in better tools, to cleaning up the source code. But which options will have the biggest impact? Drawing from the literature in software engineering and industrial/organizational psychology to identify factors that correlate with productivity, we designed a survey that asked 622 developers across 3 companies about these productivity factors and about self-rated productivity. Our results suggest that the factors that most strongly correlate with self-rated productivity were non-technical factors, such as job enthusiasm, peer support for new ideas, and receiving useful feedback about job performance. Compared to other knowledge workers, our results also suggest that software developers' self-rated productivity is more strongly related to task variety and ability to work remotely.